The Potential Benefits of Using Garlic Oil and Its Active Constituent, Dially Disulphide, in Combination With Carvedilol in Ameliorating Isoprenaline-Induced Cardiac Damage in Rats - Asdaq, Syed Mohammed Basheeruddin; Challa, Obulesu; Alamri, Abdulhakeem S.; Alsanie, Walaa F.; Alhomrani, Majid; Asad, Mohammed (Frontiers in Pharmacology, 2021)
Garlic oil and its primary component, diallyl disulphide (DADS), were tested in rats with isoprenaline (ISO) induced myocardial infarction for cardioprotective benefits when combined with carvedilol. Garlic oil (GO) was administered to rats (Sprague-dawley strain) at two doses of 50 and 100 mg/kg body weight, whereas DADS was given in two doses of 4.47 and 8.94 mg/kg, respectively. The animals were given oral doses of garlic oil and DADS on alternate days for three weeks, either alone or in combination with carvedilol (2 mg/kg). Cardiac injury was done by administering two doses of isoprenaline (150 mg/kg, sc) to all treated groups except the first, which served as a control. Biomarkers of cardiac injury and histological investigations were studied for their potential in reducing ISO-induced myocardial damage. Animals pretreated with GO, DADS, and carvedilol had significantly (P<0.01) lowered heart weight and heart to body weight ratio. In rats treated with carvedilol plus high dosages of garlic oil (100 mg/kg, p.o) and DADS (8.94 mg/kg, p.o) compared to the ISO control and carvedilol group, the activities of SOD and Catalase were enhanced in cardiac tissue homogenate. When compared to ISO control and carvedilol group, the activities of LDH and CK-MB were elevated in heart tissue homogenate with a simultaneous reduction in their serum levels in animals treated with a combination of carvedilol with high doses of garlic oil (100 mg/kg, p.o) and DADS (8.94 mg/kg, p.o). Overall, combining garlic oil or DADS with carvedilol improved the cardioprotective effect of carvedilol and protected rats from ISO-induced myocardial infarction. However, more research is needed to establish the mechanism of garlic oil and DADS interaction with carvedilol.